The Role of International Experiences in Architectural Education: Research Reflections from Thailand (EAAE Joint Publishings, 2026)
In an era defined by unprecedented connectivity and cultural exchange, the role of international travel in shaping architectural pedagogy stands as an unequivocal cornerstone of transformative learning. This autoethnographic paper offers a unique perspective on the impact of self-directed and student-led international research experiences on the mind of the young designer. This paper describes the outcomes of two distinct international student-research experiences in Thailand during the Summer of 2023.As national identities become blurred and architectural challenges become increasingly global in scope, students desire an enriching curriculum that addresses diverse built environments, traditions, and perspectives. International travel provides a unique opportunity for the next generation of designers to grow academically, professionally, and personally.In the summer of 2023, two architecture students from the same university embarked on separate research experiences in Thailand. Graduate student, Elijah, explored vernacular masonry construction methods, building upon his work in a previous design studio focused on masonry construction and rural housing in tropical climates. The observational method of research allowed for a connection with Thai people and culture that helped inform their architectural conventions. Undergraduate student, Amelia, worked on an interdisciplinary team funded by the National Science Foundation to study agricultural land use change in Eastern Thailand using remote sensing techniques.By engaging in international research, these profound experiences transcend the confines of the classroom enhancing student skills of adaptability, cross-cultural fluency, and a deep understanding of the nuanced aspects of different cultures. This underscores the significance of international travel, which is not just important but essential for the advancement of future architects and designers. The field of architectural pedagogy serves as a foundational platform through which the integration of international research can elev